ANALISIS MANAJEMEN ORGANISASI PADA PT TSP - Hendri Rasminto; Edy Siswanto; Munifah Munifah; Ahmad Mansur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze organizational management at PT TSP through the implementation of management functions including planning, organizing, leadership, and controlling. The research method used is a literature review by examining various secondary sources such as company annual reports, official documents, as well as journals and previous research relevant to organizational management, particularly in the pharmaceutical and consumer product industries. The results of the analysis show that PT TSP has a structured and integrated organizational management system, characterized by strategic planning based on SWOT analysis, a clear organizational structure, a defined division of tasks, and the application of an adaptive leadership style. In addition, the company also implements a performance control system through financial ratio measurements and effective risk management. Despite facing challenges such as intense industry competition and the impact of the Covid-19 pandemic, PT TSP is able to maintain the company's stability and performance through continuous evaluation and control. This research is expected to provide theoretical and practical contributions as a reference for similar organizations in improving the effectiveness of organizational management in a sustainable manner.